Halal Standards and Their Contributions to the Growth of Halal Economy in Malaysia and Indonesia - Rahman, Suhaimi bin Ab; Razak, Nur Izyana Binti Abd; Nusran, Muhammad (International Journal of Halal System and Sustainability https://jurnal.narotama.ac.id/https://www.spb.gba.gov.ar/campus/https://conference.trunojoyo.ac.id/https://ojs.ucp.edu.ar/https://libros.cimsur.unam.mx/https://ojs.stikesmucis.ac.id/http://medi, 2023)
The halal business grows rapidly across the world. Halal product sales are expected to grow by 28% between 2016 and 2022. This is due to the fact that many countries see halal as a new market force and a significant value offer that is capable of contributing to their individual national economies. As such, halal is also acknowledged in ASEAN as a significant economic engine for their local economies. A variety of government-led halal initiatives have been put in place by Malaysia, Indonesia, Thailand, Brunei, Singapore, and the Philippines in order to promote economic growth, especially in majority Muslim countries that have the potential to develop into halal hubs due to the high demand for halal products. Malaysia and Indonesia are no exception in terms of developing their halal standards in order to expand their halal economy both locally and globally. It is not exaggerated though to state that both countries are among the most advanced countries in terms of halal standards and is frequently referred to by other countries regarding halal matters, halal standards, and halal certification. Additionally, Malaysia's and Indonesia’s halal standards are widely utilized and implemented by numerous industry players because it is widely acknowledged and indirectly contributes to halal economic growth. However, there are not many studies regarding Malaysia and Indonesia Halal Standards and their relations to economic growth. Hence, this research is conducted to study and look deeper into the Malaysia and Indonesia Halal Standards and halal economic growth. Qualitative methods such as document review analysis and semi-structured interviews with halal experts were used to collect data for this study. According to the study's findings, halal certification and the halal standard work together to promote economic growth, notably in the halal food industry.